Rehabilitación oral con Implantes - Tacuri Guamán Nataly Silvana (2023)
ABSTRAC The present bibliographic review focused on oral rehabilitation with implants, the purpose of which was to know the importance of dental implants and determine the different prosthetic options established around these attachments, achieving functional and aesthetic oral rehabilitation in patients partially or completely. edentulous. A literature search was carried out through scientific articles from the last 10 years, this information was obtained from databases such as Google Scholar, PubMed, Elsevier, Redalyc, Scielo, Science Direct, through exclusion, inclusion, average citation count (ACC), and journal impact factor; After the application of all these tools, a total of 52 articles were obtained to carry out the systematic review. After analyzing the selected articles, it was determined that dental implants are a favorable option to rehabilitate a patient with edentulism. Based on the evidence collected, the literature shows that there are several types of prosthetic options, one of which is the fixed prosthesis on implants. within which the individual crown, bridges and full arch prosthesis are proposed, depending on the type of edentulism present in the patient; Another prosthetic option is overdentures and hybrid prostheses, which are a restoration method in completely edentulous patients. Finally, one of the advantages of implant-supported prostheses is their greater acceptance compared to conventional prostheses, because they improve the living conditions in the functional, aesthetic and psychological state of the patient. Keywords: Implant prostheses, implant impressions, implantology, Oral rehabilitation